PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2020 - Pramesti Kemala Sari; Mudasetia Mudasetia; Achmad Marzuki (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2023)
This research is a causal research that aims to analyze the effect of profitability, liquidity, leverage and firm size on earnings management. This research is a secondary research. Sources of data used in this study came from financial reports obtained from the Indonesia Stock Exchange website. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2020 period. The method of determining the sample used is the purposive sampling method. After determining the sample using the purposive sampling method, there were 24 companies that met the required sample criteria with an observation period of 4 years. Testing the hypothesis in this study using multiple regression analysis method using the SPSS application as a test tool. The analytical method used is descriptive statistical test, classical assumption test (normality test, multicollinearity test, autocorrelation test, heteroscedasticity test), and hypothesis testing. Based on the ANOVA test, the profitability variable has an influence on earnings management. While the variables of liquidity, leverage and firm size have no effect on earnings management.